Peningkatan Hasil Belajar Mata Kuliah Sejarah Gereja Melalui Media Book Creator Program Studi Pendidikan Agama Kristen Institut Agama Kristen Negeri (IAKN) Tarutung - Rawatri Sitanggang (Program Studi Pendidikan Agama Kristen, Fakultas Ilmu Pendidikan Kristen IAKN Tarutung, 2022)
History is the story of the developments and changes experienced by the church, as about those who were called by Christ to this world. Church history that needs to be studied in carrying out its vocation in the general period/period of church history. The method and technique used in this research is the R&D (Research and Development) method. Research and development methods or in English Research and Development are research methods used to produce certain products, and test the effectiveness of these products. The results obtained indicate that Media Book Creator can improve learning outcomes for the Church History course at PAK IAKN Tarutung Study Program. The conclusion obtained in the research is that the making of this Book Creator requires the ability to coordinate, collaborate with Colleagues who are lecturers in the Church History course. The advice given by the author is that in this process the author finds the importance of collaboration to facilitate integration which in the end really helps maximize public services in this case developing learning media in IAKN Tarutung student lectures.